PW 1296 Changing awareness, attitudes, and behaviours in an evidence-informed social marketing campaign to reduce recreational boating injuries in british columbia: the evidence. (November 2018) - Clemens, Tessa; Smith, Jennifer; Macpherson, Alison; Pike, Ian
Abstract : Background: Recreational boating-related injuries are a preventable cause of morbidity and mortality in Canada. Implementing a targeted social marketing campaign will encourage meaningful behaviour change and result in increased compliance with safe boating practices, and reduced incidence of injury. Objective: To provide a foundation to guide the development of a targeted boating safety social marketing campaign, this phase of the project aimed to: (1) summarize the existing evidence related to the risk factors and interventions for recreational boating-related injury; and (2) describe the burden of recreational boating-related injury in British Columbia (BC). Methods: We conducted (1) a review of the English language literature related to recreational boating injury; and (2) a retrospective analysis of fatalities, hospitalizations, and emergency department visits caused by recreational boating-related injuries in BC from April 1, 2009 – March 31, 2014. Findings: Alcohol consumption and low PFD use are widely established risk factors for recreational boating-related injury. Existing studies suggest that legislation and targeted educational initiatives may improve recreational boating safety practices and reduce injury. In BC, recreational boating-related injuries primarily occurred among adult males during the warmer months. Most injuries occurred during powerboat use. One third of individuals who were fatally injured in a recreational boating incident had consumed alcohol and the majority were not wearing a PFD at the time of the incident. Recreational boating-related deaths most frequently occurred in a lake. Conclusion: A targeted social marketing campaign aimed at improving safe boating behaviors is warranted. The campaign should include messaging related to avoiding alcohol use and wearing a PFD while boating. High-risk groups for targeted messaging include males, teenagers, young adults, and middle-aged adults. The campaign should be developed with emphasis on the flat water recreational boating community, and delivery should occur during the warmer months of the year, especially July and August.